Valmentajan ja pelaajan vuorovaikutuksen yhteys pelaajan koettuun itseluottamukseen U20 SM-sarjan jääkiekkoilijoilla - Huttu, Teemu; Järvenpää, Joel (2024)
The purpose of this study was to describe and understand the connection between coach-player interaction and player perceived self-confidence. We examined various coaching methods to support player self-confidence as well as what constitutes player self-confidence among U20 elite junior ice hockey players. In the Finnish context, ice hockey has been relatively under-researched, which is why we chose this topic, as its position as a major sport is significant.